Factor Analysis of Occupational Stressors among Academicians from Autonomous Colleges in Madhya Pradesh, India - Shrivastava, Alka (Asian Journal of Managerial Science, 2021)
Occupational stress or work stress is one of the major factors affecting employees at the workplace. It is evident from the available literature that occupational stress is present among the faculties of the higher education. It is increasing due to intense competitive pressure and new challenges in the academic environment. The objective of this paper is to identify the main factors or stressors of occupational stress among the academic faculty of higher educational institutions in India. This study was done on a sample of 400 faculty members, which was drawn randomly from different autonomous colleges of Madhya Pradesh. Exploratory factor analysis was applied for determining the stressors. The stress level was measured, and t-test was performed for data analysis. The study has confirmed five factors namely, Work-Related Stressors; Personal and professional development Stressors; Techno Stressors; Colleagues and Students Interaction Stressors and Organizational Climate Stressors. The results also revealed that major causes of occupational stress. The significant differences in stress level between Male and Female faculties and between Government and Private College faculties are also reported.